22.9k views
3 votes
6 2/5 ÷ 3 1/5 − (2 3/10 + 1 3/8)

I will award 25 points

2 Answers

4 votes
Here is the answer!!!!!!!!!!
6 2/5 ÷ 3 1/5 − (2 3/10 + 1 3/8) I will award 25 points-example-1
User Tiago Leite
by
5.5k points
5 votes


\\ \mathbb {}


\\ 6 (2)/(5) / 3 (1)/(5) - (2(3)/(10) + 1 (3)/(8) )


\\ = (32)/(5) / (16)/(5) - ( (23)/(10) + (11)/(8) )


\\ = (32)/(5) / (16)/(5) - ( (92 + 55)/(40) )


\\ = (32)/(5) / (16)/(5) - (147)/(40)


\\ = (32)/(5) * (5)/(16) - (147)/(40)


\\ = 2 - (147)/(40)


\\ = (80 - 147)/(40)


\\ = ( - 67)/(40)


\\ = - 1 (27)/(40)

User Ha Bom
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.